Amino Acid-Based Poly(ester urea) Biodegradable Membrane for Guided Bone Regeneration - Dal-Fabbro, Renan (2024)
Barrier membranes (BM) for guided bone regeneration (GBR) aim to support the osteogenic healing process of a defined bony defect by excluding epithelial (gingival) ingrowth and enabling osteoprogenitor and stem cells to proliferate and differentiate into bone tissue. Currently, the most widely used membranes for these approaches are collagen-derived, and there is a discrepancy in defining the optimal collagen membrane in terms of biocompatibility, strength, and degradation rates. Motivated by these clinical observations, we designed a collagen-free membrane based on l-valine-co-l-phenylalanine-poly(ester urea) (PEU) copolymer via electrospinning. Degradation and mechanical properties of these membranes were performed on as-spun and water-aged samples. Alveolar-bone-derived stem cells (AvBMSCs) were seeded on the PEU BM to assess their cell compatibility and osteogenic characteristics, including cell viability, attachment/spreading, proliferation, and mineralized tissue-associated gene expression. In vivo, PEU BMs were subcutaneously implanted in rats to evaluate their potential to cause inflammatory responses and facilitate angiogenesis. Finally, critical-size calvarial defects and a periodontal model were used to assess the regenerative capacity of the electrospun PEU BM compared to clinically available Cytoflex synthetic membranes. PEU BM demonstrated equal biocompatibility to Cytoflex with superior mechanical performance in strength and elasticity. Additionally, after 14 days, PEU BM exhibited a higher expression of BGLAP/osteocalcin and superior in vivo performance-less inflammation and increased CD31 and VWF expression over time. When placed in critical-sized defects in the calvaria of rats, the PEU BM led to robust bone formation with high expression of osteogenesis and angiogenesis markers. Moreover, our membrane enhanced alveolar bone and cementum regeneration in an established periodontal model after 8 weeks. We demonstrate that the PEU BM exhibits favorable clinical properties, including mechanical stability, cytocompatibility, and facilitated bone formation in vitro and in vivo. This highlights its suitability for GBR in periodontal and craniofacial bone defects.